One-year outcomes in cardiogenic shock triggered by supraventricular tachycardia: an analysis of the FRENSHOCK multicenter prospective registry - Cherbi, Miloud; Bonnefoy, Eric; Lamblin, Nicolas; Gerbaud, Edouard; Bonello, Laurent; Roubille, François; Levy, Bruno; Champion, Sebastien; Lim, Pascal; Schneider, Francis; Elbaz, Meyer; Khachab, Hadi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiogenic shock (CS) is the most severe form of heart failure (HF), resulting in high early and long-term mortality. Characteristics of CS secondary to supraventricular tachycardia (SVT) are poorly reported. Based on a large registry of unselected CS, our aim was to compare one-year outcomes between SVT-triggered and non-SVT-triggered CS. Methods: FRENSHOCK is a French prospective registry including 772 CS from 49 centers. For each patient, the investigator could report 1 to 3 CS triggers from a pre-established list (ischemic, mechanical complications, ventricular/supraventricular arrhythmia, bradycardia, iatrogenesis, infection, non-compliance, others). One-year outcomes (rehospitalizations, mortality, heart transplantation (HTx), ventricular assist devices (VAD)) were analyzed, adjusted on independent predictive factors. Results: Within 769 CS included, 100 were SVT-triggered (13%) with 65 with SVT as exclusive trigger (8.5%). SVT triggered CS patients exhibited a higher proportion of male individuals with more frequent history of cardiomyopathy or chronic kidney disease, and more profound CS (biventricular failure and multiorgan failure). At 1-year, there was no difference in all-cause mortality (43% vs 45.3%, adjusted HR of 0.9 [95% CI 0.59 – 1.39], p = 0.64), need for HTx or VAD (10% vs 10%, aOR 0.88 [0.41 – 1.88], p = 0.74) or rehospitalizations (49.4% vs 44.4%, aOR 1.24 [0.78 – 1.98], p = 0.36). Patients with SVT as exclusive trigger presented more 1-year rehospitalizations (52.8% vs 43.3%, aOR 3.74 [1.05 – 10.5], p = 0.01). Conclusion: SVT is a frequent trigger of CS alone or in association in more than 10% of miscellaneous CS. Although SVT-triggered CS patients were more comorbid with more pre-existing cardiomyopathies and HF, they presented similar rates of mortality, HTx and VAD at 1-year arguing for a better overall prognosis. NCT02703038